A Post-Analysis of the Introduction of the EU Directive 92/57/EEC in the Swedish Construction Industry - Leif Berglund; Jan Johansson; Maria Johansson; Magnus Nygren; Björn Samuelson; Magnus Stenberg (Buildings, 2022)
The EU directive 92/57/EEC focuses on ensuring that health and safety-related matters are taken into consideration during every stage of construction-related work and has been introduced into the regulations of the member countries. In 2006, Sweden was tasked by the European Commission to clarify its implementation of the directive, including which management roles and responsibilities were to come into effect during both the planning and eventual execution of construction work—changes that ultimately were introduced into the national regulations in 2009. Focusing on the accident trends in the construction industry in the years immediately following these regulatory changes, we find that the new management roles and responsibilities had no apparent effect on the accident rates. Furthermore, we argue that there is a need to broaden the analysis regarding the implementation of the EU directive 92/57/EEC to also include nation-specific changes to health and safety management and policy. These qualitative studies should also include a dedicated focus on how changes to management structures and processes may affect the prevalence of occupational diseases specifically.